(untitled) (Psychology Travelogs, 2025)
The article analyses the research on inclusive higher education and shows that the principles of designing adaptive disciplines aimed at overcoming cognitive deficits of students with disabilities are insufficiently developed. The data analysis allowed us not only to identify the applicants who are most in need of psychological and pedagogical support, but also to clarify the content of adaptive disciplines required for them. Thus, a high level of emotional comfort combined with a high rate of escapism in applicants with severe hearing impairment suggests that their emotional comfort is associated with a deficit in reflection on learning difficulties (misunderstanding the meaning of concepts, theoretical schemes, etc.). This deficit can rightly be considered as a tertiary impairment in listening-based FML. It is obvious that there is a need to individualise classes with students depending on the severity of their hearing impairment and their mastery of the means of working through learning difficulties. A higher level of prestige and dominance motives can be considered as prerequisites for overcompensation. Tracing the correlations between the indicators of social and psychological adaptation and learning motivation also allowed us to draw a number of significant conclusions about the design of adaptive disciplines. Their content should actualise the motive of creative self-development as a personal resource for overcoming learning difficulties through active mastery of means that help minimise them - the creation of cognitive schemes that promote understanding of the learning content, development of reflection on learning activities and, in particular, reflection on understanding of educational texts, use of sound-amplifying equipment, etc. The data of psychological and pedagogical monitoring allow us to give recommendations on designing the content of adaptive disciplines and practices for students with disabilities.